Examining the causes of entrepreneurial intentions and their moderating effects. (21st October 2020) - Turuk, Mladen; Horvatinović, Tin; Sudarić, Željko
Entrepreneurship plays an important role in the development of an economic system on the national and regional level. Given these findings, it is not startling that several different strands of research have been and are still being conducted on the topic of what determines individuals to create and start their business ventures. In this paper, we used the theory of planned behaviour as our theoretical foundation. Along with the conventional elements of the theory, individual's attitudes, subjective norms and perceived behavioural control, we tested additional moderating effects. The results show that attitude towards entrepreneurship and perceived behavioural control have a positive impact on entrepreneurial intentions, while the opposite is true for subjective norms. In addition, gender has a significant moderating effect only for subjective norms. Finally, subjective norms were found to moderate both the relation of attitude towards entrepreneurship and perceived behavioural control on entrepreneurial intentions.